Different Device Architectures for Bulk-Heterojunction Solar Cells - Adam, Getachew; Munkhbat, Battulga; Denk, Patrick; Ulbricht, Christoph; Hrelescu, Calin; Scharber, Markus C. (Frontiers in Materials, 2016)
We report different solar cell designs which allow a simple electrical connection of subsequent devices deposited on the same substrate. By arranging so-called standard and inverted solar-cell architectures next to each other, a serial connection of the two devices can easily be realized by a single compound electrode. In this work, we tested different interfacial layer materials like polyethylenimine (PEI) and PEDOT:PSS, and silver as a non-transparent electrode material. We also built organic light emitting diodes applying the same device designs demonstrating the versatility of applied layer stacks. The proposed design should allow the preparation of organic bulk-heterojunction modules with minimized photovoltaically inactive regions at the interconnection of individual devices.